2017
DOI: 10.1371/journal.pone.0182009
|View full text |Cite
|
Sign up to set email alerts
|

Single and combined effect of retinoic acid and rapamycin modulate the generation, activity and homing potential of induced human regulatory T cells

Abstract: Adoptive transfer of CD4+CD25+FOXP3+ regulatory T cells (Treg cells) has been successfully utilized to treat graft versus host disease and represents a promising strategy for the treatment of autoimmune diseases and transplant rejection. The aim of this study was to evaluate the effects of all-trans retinoic acid (atRA) and rapamycin (RAPA) on the number, phenotype, homing markers expression, DNA methylation, and function of induced human Treg cells in short-term cultures. Naive T cells were polyclonally stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 134 publications
(167 reference statements)
1
24
0
Order By: Relevance
“…Several reports indicate that the presentation of antigens to T cells by immature DCs results in T cell anergy or Treg induction (22). In addition, there is evidence of previous studies describing iTreg generation (23,24); however, this is the first report in which a large amount of iTregs are obtained with specificity for the antigen of interest. To achieve this, a two-step strategy was used: first, the generation of allo iTregs in co-cultures between naïve T cells and MoDC, and second, isolation of the generated iTregs and their polyclonal expansion for 6 weeks (Figure 2A).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several reports indicate that the presentation of antigens to T cells by immature DCs results in T cell anergy or Treg induction (22). In addition, there is evidence of previous studies describing iTreg generation (23,24); however, this is the first report in which a large amount of iTregs are obtained with specificity for the antigen of interest. To achieve this, a two-step strategy was used: first, the generation of allo iTregs in co-cultures between naïve T cells and MoDC, and second, isolation of the generated iTregs and their polyclonal expansion for 6 weeks (Figure 2A).…”
Section: Discussionmentioning
confidence: 91%
“…To date, there are a few published protocols on in vitro generation of human Tregs, most of them polyclonal and in short-term cultures (1-2 weeks) and some of them with no data on the methylation status of the FOXP3 gene (47)(48)(49). Other reports on polyclonal conversion showed that FOXP3 remains methylated or that Treg restimulation causes the loss of its expression (23,24,50). Among the studies describing long-term generation of allospecific iTregs, Tu et al reported the use of CD40L-stimulated B cells (NIH 3T3 cells transfected with the CD40 ligand; tCD40L NIH/3T3) as antigen-presenting cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the higher sensitivity of conventional T cells compared to Tregs to inhibition by Rapa [ 65 ] may allow for a preferential expansion of Treg-like cells despite lower total fractions of activated cells in the presence of Rapa and may explain the relatively high expression of iTreg candidate genes despite the lower CD25+ cell fraction. Very recently, Candia et al [ 66 ] re-sorted CD4 + CD25 high CD127 − cells from iTreg cultures prior to suppression assays and confirmed that human iTregs generated in the presence of Rapa had superior suppressive activity in vitro compared to the corresponding iTregs generated without Rapa. However, the in vivo relevance and functionality of iTregs is still controversial, and even iTregs generated with similar protocols are not always determined to be suppressive in vitro and/or in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, Tregs residing in the gut, which may mostly comprise pTregs and may resemble ATRA-induced iTregs, are different from Tregs in other tissues [ 16 , 41 ]. In this regard, it is important to mention that ATRA and Rapa were shown to confer differential homing capacities to murine and human iTregs [ 66 , 71 ]. It is therefore conceivable that iTregs with a certain phenotype may be suppressive in one, but not in another disease model.…”
Section: Discussionmentioning
confidence: 99%
“…RAPA was also shown to preferentially promote the expansion of CD4 + CD25 high FOXP3 + Tregs as compared to the CD4 + CD25 neg FOXP3 + Treg subset (75). Intriguingly, RAPA enhances the expression of CXCR4, the ligand of stromal-derived-factor-1 (SDF-1), which is constitutively expressed in the bone marrow, suggesting that this drug may promote the development of Tregs with distinct homing properties (99).…”
Section: Involvement Of Immune Cells In the Maintenance Of Immune Commentioning
confidence: 99%